Ketepatan pemorsian hidangan di RSUD Dr. Tjitrowardojo Purworejo - Andita Putri Astari; Setyowati Setyowati; Sri Kadaryati (AcTion: Aceh Nutrition Journal, 2021)
Maintaining food quality can be done by supervising portion standards. One of the important components in food management is the quality of human resources. The research objective was to determine the accuracy of serving dishes in terms of the characteristics of the serving staff. This observational study had a cross-sectional design. Collecting data in July 2019 at the Nutrition Installation of Dr. Tjitrowardojo Purworejo hospital. The research subjects were 14 people who were taken by a purposive sampling method. Subject characteristics consist of age, gender, level of education, and length of work. The accuracy of serving dishes was categorized into precise (±10% of standard serving) and imprecise (<10% or >10% of standard serving). The weighing method is used to determine the portion produced by the research subject. The research instrument is a digital food scale that has been calibrated at the BBKKP Calibration Laboratory with the number: 310/Labkal/V/2019. Data analysis used the Spearman Rank Correlation test. The results showed that most of the dishes were not done correctly (85,7%). Statistically, the characteristics of the serving staff do not show a correlation with the accuracy of serving dishes (p > 0,05). Concluded, there is no correlation between the characteristics of the proponents with the accuracy of the serving dishes in Dr. Tjitrowardojo Purworejo hospital.